Developing intercultural learning in Australian pre-service teachers through participating in a short term mobility program in Malaysia. (August 2017) - Hepple, Erika; Alford, Jennifer; Henderson, Deborah; Tangen, Donna; Hurwood, Mary; Alwi, Amyzar; Hassan Shaari, Zaira Abu; Alwi, Aliza
Abstract: This study investigates the intercultural learning of 10 Australian pre-service teachers participating in a short term mobility program in Malaysia. Drawing on Nussbaum's Capabilities Approach, intercultural learning is conceptualised as developing three capabilities: critical cultural self-examination; affiliation with and towards others; and building narrative imagination. Our findings confirmed that participation in this structured mobility experience promoted critical professional self-awareness regarding cultural diversity; built trust and intercultural understanding through intensive interaction with Malaysian peers; and developed participants as more culturally responsive teachers. We recommend that a structured short term mobility experience be embedded within teacher education programs. Highlights: Ten Australian pre-service teachers engaged in a mobility program in Malaysia. Intensive interaction with Malaysian peers promoted intercultural learning. Participants developed critical self-awareness, affiliation, empathy for diversity. A short term mobility program should be embedded in teacher preparation courses.